A foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material and preparation method thereof

By using a laminated composite structure of graphene and silicone prepolymer covered with foam metal and magnetic nanoparticles in the thermally conductive interface material, the orientation of graphene is controlled by using magnetic field orientation, and the thermal conductivity and flexibility in the prior art are solved Taking into account both the difficult problems, high thermal conductivity and flexibility of interface materials are achieved, extending service life and reducing costs.

CN115157714BActive Publication Date: 2025-02-25ZHEJIANG UNIV OF TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211018328.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-24
Publication Date
2025-02-25
Estimated Expiration
2042-08-24

AI Technical Summary

Technical Problem

The existing thermal interface materials are difficult to take into account both flexibility and thermal stability while improving thermal conductivity, resulting in poor thermal management when used in electronic components.

Method used

Using foam metal as the thermal conductivity framework, a laminated composite structure of graphene and silicone prepolymer coated with magnetic nanoparticles is used to accurately control the orientation arrangement of graphene by using magnetic field orientation to form an interface material with high thermal conductivity and flexibility.

Benefits of technology

It is achieved to improve the flexibility and thermal stability of the interface material without reducing thermal conductivity, extend the service life of the material, and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention provides a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material and a preparation method thereof. The present invention uses vinyl-terminated polydimethylsiloxane and methyl hydrogenated silicone oil as an organic matrix, adds magnetic particle-coated graphene oriented in a magnetic field to the organic matrix, and uses foam metal as a thermal conductive skeleton to prepare a foam metal / oriented graphene laminated composite structure thermal conductive interface material. Test results show that the composite material has high thermal conductivity while maintaining excellent flexibility and compressibility, providing a practical method for breaking through technical bottlenecks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal management, and in particular relates to a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material and a preparation method thereof. Background Art

[0002] With the continuous development of communication technology, the electronics industry is increasingly inclined to develop towards thinness, high integration and miniaturization. As the size of chips decreases, the integration and power density continue to increase, the heat generated by chips during operation is increasing, causing the temperature of the chips to continue to rise, seriously affecting the performance, reliability and life of the final electronic components. Thermal interface materials are widely used in the field of heat dissipation of electronic components. Their main function is to fill between the chip and the heat sink, and between the heat sink and the radiator to expel the air in them, so that the heat generated by the chip can be transferred to the outside more quickly through the thermal interface material, achieving the important role of reducing the operating temperature and extending the service life.

[0003] In recent years, my country's thermal interface material industry has developed rapidly, but the high-end thermal conductive material market is still occupied by developed countries such as the United States and Japan. At present, the commonly used matrices for thermal conductive interface materials are polymers and liquid metals. The polymer matrix has good fluidity and processability, but it is difficult to obtain a high thermal conductivity interface material by filling it with thermal conductive fillers; liquid metal has a high thermal conductivity coefficient, but excessive fluidity brings migration problems, causing electronic components and circuit contamination or even short circuits. Summary of the invention

[0004] In view of the above technical problems, the present invention provides a high thermal conductivity flexible interface material of a foam metal / oriented graphene laminated composite structure and a preparation method thereof.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material comprises the following steps:

[0007] S1. Preparation of graphene coated with magnetic nanoparticles: After a certain amount of graphene is dispersed in deionized water, it is treated with poly (sodium 4-styrene sulfonate) (PSS) and polydiallyldimethylammonium chloride (PDDA) for electrostatic adsorption to obtain positively charged graphene, and then negatively charged ferrosoferric oxide is added to react to obtain magnetic particle coated graphene;

[0008] S2. Preparation of graphene-containing silica gel prepolymer: weigh appropriate amounts of vinyl-terminated polydimethylsiloxane, methyl hydrogen silicone oil, catalyst, inhibitor and magnetic particle-coated graphene prepared in S1, mix and then stir in vacuum to obtain graphene silica gel prepolymer;

[0009] S3, preparation of oriented silicone sheet: transferring the graphene silicone prepolymer obtained in step S2 into a mold, and orienting it in a magnetic field until the graphene silicone prepolymer is initially solidified; drying after the initial solidification to obtain an oriented silicone sheet;

[0010] S4, coating the surface of the foam metal with graphene silica gel prepolymer: coating the surface of the foam metal plate with the graphene silica gel prepolymer obtained in step S2, and drying to obtain a coated foam metal plate;

[0011] S5. Preparation of a highly thermally conductive flexible interface material of a foam metal / oriented graphene laminate: Take the oriented silicone sheet in step S3 and the coated foam metal plate in step S4, assemble and compound them according to the structure of oriented silicone sheet / coated foam metal plate / oriented silicone sheet to obtain the highly thermally conductive flexible interface material.

[0012] In the prior art, in order to increase the thermal conductivity of silica gel, a certain amount of graphene is added to it.

[0013] In the above technical scheme of the present invention, graphene is first treated with PSS to make the graphene carry a negative charge, then the negatively charged graphene is treated with cationic polyelectrolyte PDDA to combine with ammonium ions in PDDA, and finally negatively charged ferroferric oxide particles are added to the graphene so that the ferroferric oxide particles can be combined with the surface of graphite to obtain magnetic particle-coated graphene, which is added to a silica gel prepolymer and oriented in a magnetic field, so that the graphene can be oriented in a silica gel sheet after curing; the method uses magnetic nanoparticles to coat the graphene, and uses a magnetic field induction method to accurately control the orientation of the graphene in the silica gel matrix, and the graphene composite with the ferroferric oxide particles on the surface is oriented along the magnetic field direction in an end-to-end manner. The composite has a two-dimensional planar structure and exhibits strong anisotropy, so that its thermal conductivity in the axial direction is much higher than that in the parallel direction. Under such a highly oriented arrangement condition, the amount of thermal conductive filler can be appropriately reduced to improve the flexibility of the thermal conductive interface material without reducing the thermal conductivity efficiency of the silicone sheet, thereby taking into account both the high thermal conductivity and flexibility of the thermal conductive interface material. At the same time, the ferroferric oxide particles coated on the ends of the graphene will form a bridge of ferroferric oxide particles connecting two adjacent graphenes in the end-to-end connected structure formed after orientation under the traction of the charge carried on the graphene, thereby improving the thermal stability of the silicone sheet. When overheated, the oriented arrangement of the graphene is not easily disrupted due to the expansion of the silicone sheet, thereby extending the service life of the heat dissipation material.

[0014] As a preferred embodiment of the above technical solution of the present invention, in step S1, the amount of ferrosoferric oxide used is 0.02% to 0.1% of the content of the graphene.

[0015] As a preferred embodiment of the above technical solution of the present invention, in step S3, the magnetic field strength is 0.5T~6T.

[0016] As a preferred embodiment of the above technical solution of the present invention, in step S3, the direction of the magnetic field is perpendicular to the plane of the foam metal plate or the plane of the mold.

[0017] As a preferred embodiment of the above technical solution of the present invention, in step S1, the mass ratio of PSS to graphene is 10%~50%; the mass ratio of PDDA to graphene is 10%~50%.

[0018] As a preferred embodiment of the above technical solution of the present invention, in step S2, the content of graphene coated with the magnetic particles is 5% to 25%.

[0019] As a preferred embodiment of the above technical solution of the present invention, in step S2, the viscosity of the vinyl-terminated polydimethylsiloxane is in the range of 500-30000 mPa·s, and the content is 70%-80%;

[0020] As a preferred embodiment of the above technical solution of the present invention, in step S2, the viscosity of the methyl hydrogen silicone oil is in the range of 50-600 mPa·s, and the content is in the range of 0.4%-8%;

[0021] As a preferred embodiment of the above technical solution of the present invention, in step S2, the catalyst is selected from Custer platinum catalyst, the content of which is 0.03% to 0.8%, and the effective concentration of platinum is 0.5% to 1.0%;

[0022] As a preferred embodiment of the above technical solution of the present invention, in step S2, the inhibitor is preferably 1-ethynylcyclohexanol, and its content is 0.05% to 1% of the sum of the mass of the vinyl-terminated polydimethylsiloxane and the methyl hydrogen silicone oil.

[0023] Another object of the present invention is to provide a high thermal conductivity flexible interface material of a foam metal / oriented graphene laminated composite, which is prepared according to the above-mentioned method for preparing a high thermal conductivity flexible interface material of a foam metal / oriented graphene laminated composite. The interface material includes an intermediate skeleton layer and a thermally conductive silicone layer arranged on the upper and lower surfaces of the intermediate skeleton layer, graphene is added to the thermally conductive silicone layer, and the graphene is oriented in an external magnetic field and arranged in a directional manner.

[0024] In the above technical solution of the present invention, the present invention uses vinyl-terminated polydimethylsiloxane and methyl hydrogen silicone oil as organic matrices, magnetic particle-coated graphene oriented in a magnetic field as thermal conductive filler, and foam metal as a thermal conductive skeleton to prepare a foam metal / oriented graphene laminated composite structure thermal conductive interface material. Test results show that the composite material has high thermal conductivity while maintaining excellent flexibility and compressibility, providing a practical method for breaking through technical bottlenecks.

[0025] As a preferred embodiment of the above technical solution of the present invention, the material of the intermediate skeleton layer is selected from one of foamed nickel, foamed copper, foamed titanium, foamed cobalt, foamed tungsten, foamed molybdenum, foamed chromium, foamed iron nickel, and foamed aluminum.

[0026] As a preferred embodiment of the above technical solution of the present invention, the thickness of the intermediate skeleton layer is 0.15-0.30 mm.

[0027] As a preferred embodiment of the above technical solution of the present invention, the thickness of the thermally conductive silicone layer is 1.0-1.5 mm.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The thermal interface material of the present invention uses flexible foam metal as a thermally conductive skeleton and is laminated with a thermally conductive silicone sheet containing oriented graphene to construct a multi-level continuous thermal conductive path, thereby effectively improving the thermal conductivity of the material;

[0030] 2. The present invention uses magnetic nanoparticles to coat graphene, and uses a magnetic field induction method to accurately control the orientation of graphene in a silica gel matrix to achieve vertical oriented arrangement of graphene; the ultra-high thermal conductivity of oriented graphene is used to further reduce the amount of thermal conductive filler, while taking into account the high thermal conductivity and flexibility of the thermal conductive interface material;

[0031] 3. The thermal interface material prepared by the present invention has a stable structure and a longer service life;

[0032] 4. The present invention adopts a series of molding processes such as magnetic field orientation, coating, and thermal curing molding to in-situ prepare a thermal conductive interface material of a foam metal / graphene laminated composite structure. The process is simple, the production efficiency is high, the cost is low, and it is green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the structure of the thermal conductive interface material of the present invention;

[0034] In the figure, 1-middle skeleton layer, 2-thermal conductive silicone layer, 21-graphene. DETAILED DESCRIPTION

[0035] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited thereto.

[0036] A method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material comprises the following steps:

[0037] S1. Preparation of graphene coated with magnetic nanoparticles: After dispersing a certain amount of graphene in deionized water, the graphene is electrostatically adsorbed with poly (sodium 4-styrene sulfonate) (PSS) and polydiallyldimethylammonium chloride (PDDA) in sequence to obtain graphene coated with positive charge, and then ferrosoferric oxide with negative charge is added to react to obtain graphene coated with magnetic particles;

[0038] S2. Preparation of graphene-containing silica gel prepolymer: weigh appropriate amounts of vinyl-terminated polydimethylsiloxane, methyl hydrogen silicone oil, catalyst, inhibitor and magnetic particle-coated graphene prepared in S1, mix and then stir in vacuum to obtain graphene silica gel prepolymer;

[0039] S3, preparation of oriented silicone sheet: transferring the graphene silicone prepolymer obtained in step S2 into a mold, and orienting it in a magnetic field until the graphene silicone prepolymer is initially solidified; drying after the initial solidification to obtain an oriented silicone sheet;

[0040] S4, coating the surface of the foam metal with graphene silica gel prepolymer: coating the surface of the foam metal plate with the graphene silica gel prepolymer obtained in step S2, and drying to obtain a coated foam metal plate;

[0041] S5. Preparation of a highly thermally conductive flexible interface material of a foam metal / oriented graphene laminate: Take the oriented silicone sheet in step S3 and the coated foam metal plate in step S4, assemble and compound them according to the structure of oriented silicone sheet / coated foam metal plate / oriented silicone sheet to obtain the highly thermally conductive flexible interface material.

[0042] Wherein, step S1 comprises the following steps:

[0043] Step 1: Weigh 5-25 g of graphene and 0.8-7.5 g of PSS poly(sodium 4-styrene sulfonate) into a beaker, add an appropriate amount of deionized water, and stir magnetically for 30 min;

[0044] Step 2: The mixed solution prepared in step 1 was ultrasonically dispersed for 30 minutes, and then placed in an oven for 12 hours at a temperature of 50°C;

[0045] Step 3: Place the mixed solution after the insulation in step 2 in a high-speed centrifuge and centrifuge it for 3 times at a speed of 12000r / min, 30min each time. After the centrifugation, remove the upper clear liquid to remove PSS and keep the lower solution;

[0046] Step 4: Add 0.8-4.5 g PDDA (polydiallyl dimethyl ammonium chloride) to the solution in step 3, add an appropriate amount of deionized water, and stir magnetically for 30 minutes;

[0047] Step 5: The mixed solution in step 4 was subjected to ultrasonic dispersion treatment for 30 minutes, and then centrifuged at high speed for 3 times at 12000 r / min, each time for 30 minutes. After the centrifugation, the upper clear liquid was removed, the PDDA was removed, and the lower solution was retained;

[0048] Step 6: Add 0.005-0.25 g of ferroferric oxide to the mixed solution in step 5 and stir magnetically for 30 minutes to obtain graphene coated with magnetic particles.

[0049] Step S2 includes the following steps:

[0050] Step 7: Vacuum stirring. Weigh appropriate amounts of vinyl-terminated polydimethylsiloxane, methyl hydrogenated silicone oil, Custer platinum catalyst, and inhibitor, and add appropriate amounts of magnetic particle-coated graphene prepared in step (i) to the above mixture. Vacuum stir in a planetary mixer for 1 hour to obtain a graphene silica gel prepolymer;

[0051] The content of the graphene coated with the magnetic particles is 5% to 25%. The viscosity of the vinyl-terminated polydimethylsiloxane is in the range of 500 to 30,000 mPa·s, and the content is 70% to 80%; the viscosity of the methyl hydrogen-containing silicone oil is in the range of 50 to 600 mPa·s, and the content is 0.4% to 8%; the catalyst is selected from the Custer platinum catalyst, and its content is 0.03% to 0.8%, and the effective concentration of platinum is 0.5% to 1.0%; the inhibitor is selected from 1-ethynyl cyclohexanol, and the content is 0.05% to 1% of the sum of the mass of the vinyl-terminated polydimethylsiloxane and the methyl hydrogen-containing silicone oil.

[0052] Step S3 includes the following steps:

[0053] Step 8: Magnetic field orientation. The graphene silicone prepolymer obtained in step S2 is transferred to a polytetrafluoroethylene mold, and oriented in a magnetic field perpendicular to the mold. The magnetic field intensity is 0.5T~6T, and the orientation time is 12h, until the graphene silicone prepolymer is initially solidified;

[0054] Step 9: Drying. The graphene silica gel prepolymer prepared in step 2 is placed in an oven for drying, with the temperature set to 85°C and the time set to 6 hours to obtain a pre-cured magnetic graphene oriented silica gel sheet;

[0055] Step S4 includes the following steps:

[0056] Step 10: coating. The graphene silicone prepolymer prepared in step S2 is evenly coated on the surface of the metal foam by a coating process; the amount of graphene silicone prepolymer coated on the surface of the metal foam in this step is very small, so that the metal foam and the silicone sheet can obtain a better adhesion effect when thermal curing and bonding are performed in step S5, and the bonding strength of the obtained composite material is higher.

[0057] Step 11: Dry in an oven, set the temperature to 80°C and the time to 2h.

[0058] Step S5 includes the following steps:

[0059] Step 12: Take the coated foam metal plate in step 11 and the oriented silicone sheet in step 9 and assemble them into embryos according to the structure of oriented silicone sheet / coated foam metal plate / oriented silicone sheet;

[0060] Step 13: Place the embryo in step 12 into a flat vulcanizer for thermal curing, with the temperature set to 155° C., the pressure to 15 MPa, and the curing time to 10 min, to obtain a highly thermally conductive flexible interface material of a foam metal / oriented graphene laminated composite structure.

[0061] Another object of the present invention is to provide a highly thermally conductive and flexible interface material of a foam metal / oriented graphene laminate, which is prepared according to the above-mentioned preparation method. The interface material comprises an intermediate skeleton layer 1 and a thermally conductive silicone layer 2 arranged on the upper and lower surfaces of the intermediate skeleton layer. Graphene 21 is added to the thermally conductive silicone layer, and at least part of the graphene molecules are oriented in the same manner; the thickness of the intermediate skeleton layer is 0.15~0.30mm, and the thickness of the thermally conductive silicone layer is 1.0~1.5mm.

[0062] The material of the intermediate skeleton layer 1 is selected from one of foamed nickel, foamed copper, foamed titanium, foamed cobalt, foamed tungsten, foamed molybdenum, foamed chromium, foamed iron nickel, and foamed aluminum; further, the flexible foam metal is foamed copper or foamed nickel. The porosity of the foamed metal is 60% to 80%, and the average pore size is 8 μm to 1 mm.

[0063] Example 1

[0064] A method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material comprises the following steps:

[0065] 1. Preparation of magnetic nanoparticles coated with graphene

[0066] Step 1: Weigh 5 g of graphene and 0.8 g of PSS (poly(sodium 4-styrene sulfonate)) into a beaker, add an appropriate amount of deionized water, and stir magnetically for 30 min;

[0067] Step 2: Ultrasonic disperse the mixed solution prepared in step 1 for 30 minutes, and then put it into an oven for drying for 12 hours at a temperature set at 50°C;

[0068] Step 3: Place the mixed solution dried in step 2 in a high-speed centrifuge and centrifuge for 3 times at a speed of 12000r / min, 30min each time. After the centrifugation, remove the upper clear liquid, remove the PSS, and retain the lower solution;

[0069] Step 4: Add 0.8 g PDDA (polydiallyl dimethyl ammonium chloride) to the solution in step 3, add an appropriate amount of deionized water, and stir magnetically for 30 minutes;

[0070] Step 5: The mixed solution in step 4 was subjected to ultrasonic dispersion treatment for 30 minutes, and then centrifuged at high speed for 3 times at 12000 r / min, each time for 30 minutes. After the centrifugation, the upper clear liquid was removed, the PDDA was removed, and the lower solution was retained;

[0071] Step 6: Add 0.05 g of ferrosoferric oxide to the mixed solution in step 5 and stir magnetically for 30 minutes to obtain graphene coated with magnetic particles.

[0072] (II) Preparation of thermally conductive silicone sheet containing oriented graphene

[0073] Step 1: Vacuum stirring. Weigh 84g of vinyl-terminated polydimethylsiloxane, 6g of methyl hydrogenated silicone oil, 0.80g of Custer platinum catalyst, and 0.63g of inhibitor, and add 8g of the magnetic particle-coated graphene prepared above to the above mixture. Vacuum stir in a planetary mixer for 1h to obtain a graphene silica gel prepolymer;

[0074] Step 2: Magnetic field orientation. The graphene silicone prepolymer obtained in step 1 is transferred to a polytetrafluoroethylene mold and oriented in a magnetic field perpendicular to the mold. The magnetic field intensity is 2T and the orientation time is 12 hours until the graphene silicone prepolymer is initially solidified.

[0075] Step 3: Drying: The entire device of step 2 is placed in an oven for drying, with the temperature set to 85° C. and the drying time set to 6 hours to obtain an oriented silica gel sheet containing oriented graphene.

[0076] (III) Graphene silicone prepolymer coating on the surface of flexible copper foam

[0077] Step 1: Vacuum stirring. Weigh 84 g of vinyl-terminated polydimethylsiloxane, 6 g of methyl hydrogenated silicone oil, 0.80 g of Custer platinum catalyst, and 0.63 g of inhibitor, add 5 g of magnetic particle-coated graphene prepared in step (i) to the mixture, and vacuum stir in a planetary mixer for 1 h to obtain a graphene silica gel prepolymer;

[0078] Step 2: coating. Using a coating process, 5 g of the graphene silica gel prepolymer prepared in step 1 is evenly coated on the surface of the foam copper;

[0079] Step 3: Drying. The material prepared in step 2 is placed in an oven for drying to obtain a coated foam metal plate. The temperature is set at 80°C and the drying time is 2 hours.

[0080] (IV) Preparation of thermal conductive interface materials of foam copper / oriented graphene laminated composite structure

[0081] Step 1: Lamination. Take the coated foam metal sheet and the oriented silicone sheet and assemble them into a structure of oriented silicone sheet / coated foam metal sheet / oriented silicone sheet;

[0082] Step 2: Thermal curing molding. The embryo in step 1 is placed in a flat vulcanizer for thermal curing, the temperature is set to 155°C, the pressure is 15MPa, and the curing time is 10min, to obtain a thermally conductive interface material of a foam copper / oriented graphene laminated composite structure; the interface material comprises an intermediate skeleton layer 1 and a thermally conductive silicone layer 2 arranged on the upper and lower surfaces of the intermediate skeleton layer, graphene 21 is added to the thermally conductive silicone layer, and at least part of the graphene molecules are oriented in the same manner; the thickness of the intermediate skeleton layer is 0.15mm, and the thickness of the thermally conductive silicone layer is 1.0mm; the material of the intermediate skeleton layer 1 is foam copper.

[0083] Example 2

[0084] (I) Preparation of magnetic nanoparticles coated with graphene: Same as Example 1

[0085] (II) Preparation of thermally conductive silicone sheet containing oriented graphene

[0086] Step 1: Vacuum stirring. Weigh 80g of vinyl-terminated polydimethylsiloxane, 5g of methyl hydrogenated silicone oil, 0.65g of Custer platinum catalyst, and 0.64g of inhibitor, and add 15g of the magnetic particle-coated graphene prepared above to the above mixture. Vacuum stir in a planetary mixer for 1h to obtain a graphene silica gel prepolymer;

[0087] Step 2: Magnetic field orientation. The graphene silicone prepolymer obtained in step 1 is transferred to a polytetrafluoroethylene mold and oriented in a magnetic field with a magnetic field intensity of 3.5 T and an orientation time of 12 hours until the graphene silicone prepolymer is initially solidified;

[0088] Step 3: Drying: The entire device of step 2 is placed in an oven for drying, with the temperature set to 85° C. and the time set to 6 hours to obtain a thermally conductive silicone sheet containing oriented graphene.

[0089] (III) Graphene silicone prepolymer coating on the surface of flexible copper foam

[0090] Step 1: Vacuum stirring. Weigh 80g of vinyl-terminated polydimethylsiloxane, 5g of methyl hydrogenated silicone oil, 0.65g of Custer platinum catalyst, 0.64g of inhibitor, and add 15g of magnetic particle-coated graphene prepared in step (i) to the above mixture. Vacuum stir in a planetary mixer for 1h to obtain a graphene silica gel prepolymer;

[0091] Step 2: coating. Using a coating process, 5 g of the graphene silica gel prepolymer prepared in step 1 is evenly coated on the surface of the foam copper;

[0092] Step 3: Drying. Place the material prepared in step 2 in an oven and dry it at 80°C for 2 hours.

[0093] (IV) Preparation of thermal conductive interface materials of foam copper / oriented graphene laminated composite structure

[0094] Step 1: Lamination. Take the coated foam metal sheet and the oriented silicone sheet and assemble them into a structure of oriented silicone sheet / coated foam metal sheet / oriented silicone sheet;

[0095] Step 2: Thermal curing molding. The embryo in step 1 is placed in a flat vulcanizer for thermal curing, the temperature is set to 155°C, the pressure is 15MPa, and the curing time is 10min, to obtain a thermally conductive interface material of a foam copper / oriented graphene laminated composite structure; the interface material comprises an intermediate skeleton layer 1 and a thermally conductive silicone layer 2 arranged on the upper and lower surfaces of the intermediate skeleton layer, graphene 21 is added to the thermally conductive silicone layer, and at least part of the graphene molecules are oriented in the same manner; the thickness of the intermediate skeleton layer is 0.15mm, and the thickness of the thermally conductive silicone layer is 1.0mm; the material of the intermediate skeleton layer 1 is foam copper.

[0096] Example 3

[0097] (I) Preparation of magnetic nanoparticles coated with graphene: Same as Example 1

[0098] (II) Preparation of thermally conductive silicone sheet containing oriented graphene

[0099] Step 1: Vacuum stirring. Weigh 76g of vinyl-terminated polydimethylsiloxane, 4.5g of methyl hydrogenated silicone oil, 0.70g of Custer platinum catalyst, and 0.68g of inhibitor, and add 20g of the magnetic particle-coated graphene prepared above to the above mixture. Vacuum stir in a planetary mixer for 1h to obtain a graphene silica gel prepolymer;

[0100] Step 2: Magnetic field orientation. The graphene silicone prepolymer obtained in step 1 is transferred to a polytetrafluoroethylene mold and oriented in a magnetic field. The magnetic field intensity is 5T and the orientation time is 12 hours until the graphene silicone prepolymer is initially solidified;

[0101] Step 3: Drying: The entire device of step 2 is placed in an oven for drying, with the temperature set to 85° C. and the time set to 6 hours to obtain a thermally conductive silicone sheet containing oriented graphene.

[0102] (III) Graphene silicone prepolymer coating on the surface of copper foam

[0103] Step 1: Vacuum stirring. Weigh 76g of vinyl-terminated polydimethylsiloxane, 4.5g of methyl hydrogenated silicone oil, 0.70g of Custer platinum catalyst, and 0.68g of inhibitor, and add 20g of magnetic particle-coated graphene prepared in step (i) to the above mixture. Vacuum stir in a planetary mixer for 1h to obtain a graphene silica gel prepolymer;

[0104] Step 2: coating. Using a coating process, 5 g of the graphene silica gel prepolymer prepared in step 1 is evenly coated on the surface of the foam copper;

[0105] Step 3: Drying. Place the material prepared in step 2 in an oven and dry it at 80°C for 2 hours.

[0106] (IV) Preparation of thermal conductive interface materials of foam copper / oriented graphene laminated composite structure

[0107] Step 1: Lamination. Take the coated foam metal sheet and the oriented silicone sheet and assemble them into a structure of oriented silicone sheet / coated foam metal sheet / oriented silicone sheet;

[0108] Step 2: Thermal curing molding. The embryo in step 1 is placed in a flat vulcanizer for thermal curing, the temperature is set to 155°C, the pressure is 15MPa, and the curing time is 10min, to obtain a thermally conductive interface material of a foam copper / oriented graphene laminated composite structure; the interface material comprises an intermediate skeleton layer 1 and a thermally conductive silicone layer 2 arranged on the upper and lower surfaces of the intermediate skeleton layer, graphene 21 is added to the thermally conductive silicone layer, and at least part of the graphene molecules are oriented in the same manner; the thickness of the intermediate skeleton layer is 0.15mm, and the thickness of the thermally conductive silicone layer is 1.0mm; the material of the intermediate skeleton layer 1 is foam copper.

[0109] Example 4

[0110] (I) Preparation of magnetic nanoparticles coated with graphene: Same as Example 1

[0111] (II) Preparation of thermally conductive silicone sheet containing oriented graphene

[0112] Step 1: Vacuum stirring. Weigh 70g of vinyl-terminated polydimethylsiloxane, 4g of methyl hydrogenated silicone oil, 0.64g of Custer platinum catalyst, and 0.60g of inhibitor, and add 25g of the magnetic particle-coated graphene prepared above to the above mixture. Vacuum stir in a planetary mixer for 1h to obtain a graphene silica gel prepolymer;

[0113] Step 2: Magnetic field orientation. The graphene silicone prepolymer obtained in step 1 is transferred to a polytetrafluoroethylene mold and oriented in a magnetic field. The magnetic field intensity is 6T and the orientation time is 12 hours until the graphene silicone prepolymer is initially solidified;

[0114] Step 3: Drying: The entire device of step 2 is placed in an oven for drying, with the temperature set to 85° C. and the time set to 6 hours to obtain a thermally conductive silicone sheet containing oriented graphene.

[0115] (III) Graphene silicone prepolymer coating on the surface of copper foam

[0116] Step 1: Vacuum stirring. Weigh 70g of vinyl-terminated polydimethylsiloxane, 4g of methyl hydrogenated silicone oil, 0.64g of Custer platinum catalyst, and 0.60g of inhibitor, and add 25g of magnetic particle-coated graphene prepared in step (i) to the above mixture. Vacuum stir in a planetary mixer for 1h to obtain a graphene silica gel prepolymer;

[0117] Step 2: coating. Using a coating process, 5 g of the graphene silica gel prepolymer prepared in step 1 is evenly coated on the surface of the foam copper;

[0118] Step 3: Drying. Place the material prepared in step 2 in an oven and dry it at 80°C for 2 hours.

[0119] (IV) Preparation of thermal conductive interface materials of foam copper / oriented graphene laminated composite structure

[0120] Step 1: Lamination. Take the coated foam metal sheet and the oriented silicone sheet and assemble them into a structure of oriented silicone sheet / coated foam metal sheet / oriented silicone sheet;

[0121] Step 2: Thermal curing molding. The embryo in step 1 is placed in a flat vulcanizer for thermal curing, the temperature is set to 155°C, the pressure is 15MPa, and the curing time is 10min, to obtain a thermally conductive interface material of a foam copper / oriented graphene laminated composite structure; the interface material comprises an intermediate skeleton layer 1 and a thermally conductive silicone layer 2 arranged on the upper and lower surfaces of the intermediate skeleton layer, graphene 21 is added to the thermally conductive silicone layer, and at least part of the graphene molecules are oriented in the same manner; the thickness of the intermediate skeleton layer is 0.15mm, and the thickness of the thermally conductive silicone layer is 1.0mm; the material of the intermediate skeleton layer 1 is foam copper.

[0122] Comparative Example

[0123] Compared with Example 3, except that the magnetic field orientation is not performed on the graphene coated with the magnetic particles in step (ii), other conditions remain unchanged.

[0124] With respect to the above-mentioned Examples 1 to 4 and the comparative example, the inventors conducted the following experiments:

[0125] The thermal conductivity was measured using a guarded hot plate thermal conductivity instrument using the ASTM D5470 standard. The specimen was a circular sample with a thickness of 3 mm and a diameter of 100 mm. The test was repeated three times and the average value was taken.

[0126] The density test was measured using the balance method, the test adopted the GB4472-84 standard, the sample was a square sample with a thickness of 3mm and a side length of 50mm, the test was repeated three times and the average value was taken.

[0127] The Shore hardness test was performed using a Shore hardness tester in accordance with ASTM D2240 standard. The specimen was a square specimen with a thickness of 5 mm and a side length of 50 mm. The test was repeated three times and the average value was taken.

[0128] The breakdown voltage is tested using an electrical strength tester in accordance with ASTM D149 standard. The test sample is a round sample with a thickness of 1 mm and a diameter of 25 mm. 8 to 10 test points are measured and the average value is taken.

[0129] The test results are as follows:

[0130]

[0131] Compared with Example 1, Example 2 increases the content of magnetic particle-coated graphene and the magnetic field strength. Thanks to the high thermal conductivity of oriented graphene, according to the test results, the prepared composite material has improved thermal conductivity and hardness compared with Example 1, but the breakdown voltage is reduced, which is affected by the conductivity of graphene and foam copper.

[0132] Compared with Example 2, Example 3 further increases the content of magnetic particle-coated graphene and the magnetic field strength. According to the test results, the thermal conductivity and hardness are further improved, but the breakdown voltage is further reduced;

[0133] Compared with Example 3, Example 4 further improves the content of graphene coated with magnetic particles and the magnetic field strength. According to the test results, the thermal conductivity is reduced. The inventors analyze that this is because the content of graphene coated with magnetic particles is too high, and the magnetic field cannot fully orient it; in addition, too much graphene coated with magnetic particles is difficult to disperse in the organic matrix and is easy to agglomerate. These unfavorable factors affect the thermal conductivity of the composite material. On the other hand, compared with Example 3, Example 4 further improves the hardness and reduces the breakdown voltage.

[0134] Compared with Example 3, the comparative example adopts graphene coated with unoriented magnetic particles as a thermal conductive filler, and the other conditions remain unchanged. According to the test results, the thermal conductivity of the prepared composite material is greatly reduced compared with that of Example 3. This is because the graphene coated with unoriented magnetic particles cannot construct a thermal conductive path in the vertical direction, which reduces the thermal conductivity of the composite material. At the same time, the thermal conductivity of the composite material prepared by the comparative example is also much lower than that of other examples, which further confirms that the graphene coated with magnetic particles oriented in the magnetic field can effectively construct a thermal conductive path in the organic matrix, forming a good synergistic effect with the copper foam.

[0135] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, any modification, equivalence, replacement and improvement of the filler ratio and processing method involved in the present invention are included in the protection scope of the present invention.

Claims

1. A method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material, comprising the following steps: S1. Preparation of graphene coated with magnetic nanoparticles: After dispersing a certain amount of graphene in deionized water, the graphene is electrostatically adsorbed with poly (sodium 4-styrene sulfonate) (PSS) and polydiallyldimethylammonium chloride (PDDA) in sequence to obtain positively charged graphene, and then negatively charged ferrosoferric oxide is added to react to obtain magnetic particle coated graphene; S2. Preparation of graphene-containing silica gel prepolymer: weigh appropriate amounts of vinyl-terminated polydimethylsiloxane, methyl hydrogen silicone oil, catalyst, inhibitor and magnetic particle-coated graphene prepared in S1, mix and then stir in vacuum to obtain graphene silica gel prepolymer; S3, preparation of oriented silicone sheet: transferring the graphene silicone prepolymer obtained in step S2 into a mold, and orienting it in a magnetic field until the graphene silicone prepolymer is initially solidified; drying after the initial solidification to obtain an oriented silicone sheet; S4, coating the surface of the foam metal with graphene silica gel prepolymer: coating the surface of the foam metal plate with the graphene silica gel prepolymer obtained in step S2, and drying to obtain a coated foam metal plate; S5, preparation of a highly thermally conductive flexible interface material of a foam metal / oriented graphene laminate: taking the oriented silicone sheet in step S3 and the coated foam metal plate in step S4, assembling and compounding them according to the structure of oriented silicone sheet / coated foam metal plate / oriented silicone sheet to obtain the highly thermally conductive flexible interface material; The porosity of the foam metal is 60% to 80%, and the average pore diameter is 8 μm to 1 mm.

2. The method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material according to claim 1, characterized in that: In step S1, the amount of ferrosoferric oxide used is 0.02% to 0.1% of the content of the graphene.

3. The method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material according to claim 1, characterized in that: In step S3, the magnetic field strength is 0.5T to 6T.

4. The method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material according to claim 1, characterized in that: In step S3, the direction of the magnetic field is perpendicular to the mold plane.

5. The method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material according to claim 1, characterized in that: In step S1, the mass ratio of PSS to graphene is 10% to 50%; the mass ratio of PDDA to graphene is 10% to 50%.

6. The method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material according to claim 1, characterized in that: In step S2, the content of graphene coated with the magnetic particles is 5% to 25%.

7. A foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material, characterized in that: The method for preparing a highly thermally conductive flexible interface material of a foam metal / oriented graphene laminate composite according to any one of claims 1 to 6, wherein the interface material comprises an intermediate skeleton layer and a thermally conductive silicone layer arranged on the upper and lower surfaces of the intermediate skeleton layer, graphene is added to the thermally conductive silicone layer, and at least part of the graphene is oriented in an external magnetic field.

8. The method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material according to claim 7, characterized in that: The material of the intermediate skeleton layer is selected from one of foamed nickel, foamed copper, foamed titanium, foamed cobalt, foamed tungsten, foamed molybdenum, foamed chromium, foamed iron nickel, and foamed aluminum.

9. The method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material according to claim 7, characterized in that: The thickness of the intermediate skeleton layer is 0.15-0.30 mm.

10. The method for preparing a foam metal / oriented graphene laminated composite high thermal conductivity flexible interface material according to claim 7, characterized in that: The thickness of the thermally conductive silicone layer is 1.0-1.5 mm.

Citation Information

Patent Citations

  • Multilayer graphite sheet high thermal conductivity material with foam metal interlayers and preparation method of multilayer graphite sheet high thermal conductivity material

    CN108000977A

  • Method for preparing magnetic oriented graphene thermal-conductive silicone rubber composite material

    CN109943075A

  • Foam metal-based compact heat-conducting silica gel composite material with three-dimensional skeleton structure and preparation method thereof

    CN112940510A